2019
DOI: 10.1007/s00192-019-03975-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence after uncomplicated spontaneous vaginal birth in primiparous women during the first year after birth

Abstract: Introduction and hypothesis Urinary incontinence (UI) is associated with pregnancy and parity and can cause health problems for women. Our objective was to explore risk factors for UI and its effect on women's daily activities, psychological health and wellbeing 9-12 months postpartum in a low-risk primiparous population. Methods In this prospective cohort study, first-time mothers in a low-risk population with a spontaneous vaginal birth reported the occurrence of UI and its effect on daily activities and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…The absence of anticipatory contraction of the PFM during coughing together with the observed bladder descent may be related to the high prevalence of PFD symptoms (74%) in this population of primiparous women, with UI (46.9%) being the most frequent. The prevalence of UI found in this study coincided with that described by Ahlund et al [ 27 ] in primiparous women with uncomplicated delivery one year after delivery, which reported that stress UI is the most prevalent PFD in the puerperium, with no relationship found between its occurrence and obstetric factors, such as duration of the delivery, infant weight, or infant’s head circumference. Other studies have associated the appearance of stress UI in the puerperium with the presence of symptoms before or during pregnancy and with obesity [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…The absence of anticipatory contraction of the PFM during coughing together with the observed bladder descent may be related to the high prevalence of PFD symptoms (74%) in this population of primiparous women, with UI (46.9%) being the most frequent. The prevalence of UI found in this study coincided with that described by Ahlund et al [ 27 ] in primiparous women with uncomplicated delivery one year after delivery, which reported that stress UI is the most prevalent PFD in the puerperium, with no relationship found between its occurrence and obstetric factors, such as duration of the delivery, infant weight, or infant’s head circumference. Other studies have associated the appearance of stress UI in the puerperium with the presence of symptoms before or during pregnancy and with obesity [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the literature, regarding parity, vaginal delivery, and UI, as parity increases, incontinence symptoms increase (20,21). Exercises that strengthen the pelvic floor have a positive effect on UI symptoms in women (22).…”
Section: Discussionmentioning
confidence: 99%
“…Women are susceptible to involuntary leakage of urine due to their urinary system anatomy [3]. Moreover, some studies reported the relationship between demographic and midwifery factors such as age, parity, and delivery method with urinary incontinence [4][5][6].…”
Section: Introductionmentioning
confidence: 99%